How traditional Chinese medicine can prevent recurrence of common bile duct stones after endoscopic retrograde cholangiopancreatography? - Bian, Haoyu; Zhang, Liping; Yao, Yupu; Lv, Fuqi; Wei, Jiaoyang (Frontiers in Pharmacology, 2024)
Common bile duct stones, as a type of cholelithiasis, are a benign biliary obstruction that easily acute abdominalgia, and Endoscopic Retrograde Cholangiopancreatography (ERCP) is usually the first choice for clinical treatment. However, the increasing recurrence rate of patients after treatment is troubling clinicians and patients. For the prevention of recurrence after ERCP, there is no guideline to provide a clear drug regimen, traditional Chinese medicine however has achieved some result in the treatment of liver-related diseases based on the “gut-liver-bile acid axis”. On the basis of this, this article discusses the possibility of traditional Chinese medicine to prevent common bile duct stones (CBDS) after ERCP, and we expect that this article will provide new ideas for the prevention of recurrence of CBDS and for the treatment of cholelithiasis-related diseases with traditional Chinese medicine in future clinical and scientific research.